Pola Pikir Masyarakat Dalam Memajukan Usaha Batu Bata Melalui Media Sosial - Kaok, Maria; Djanggo, Romualdus T.P.M (Universitas Musamus,Merauke,Papua, 2024)
The study aims to analyze the Mindset of the Kemangi Village Community in Advancing Brick Business as a Village MSME Through Social Media. The population in this study is the Kemangi village community who have a brick business. This research is a descriptive quantitative study with a sampling technique using simple random sampling. The data collection method is carried out by observation, interviews, documentation and questionnaires, then after the data is collected, it is continued with data analysis using descriptive statistical data analysis with validity and reliability tests using spss 23. The results of the study on 30 respondents showed that r count> r table. The validity test was carried out with spss 23 software, it was declared valid for all statement items and the reliability results were declared reliable because the cronbach alpha value ≥ 0.60 was 0.757.